Unveiling the Role of Al2O3 Interlayer in Indium–Gallium–Zinc–Oxide Transistors. Issue 6 (15th January 2021) - Kim, Tae Hyeon; Park, Woojin; Oh, Seyoung; Kim, So-Young; Yamada, Naohito; Kobayashi, Hikaru; Jang, Hye Yeon; Nam, Jae Hyeon; Habazaki, Hiroki; Lee, Byoung Hun; Cho, Byungjin
Abstract : Although insertion of a thin insulating layer between metal electrodes and a semiconducting channel is an effective way to improve device performance, the exact reason for improvement in performance is not elucidated. Herein, the role of an Al2 O3 interlayer sandwiched between Al metal electrodes and an amorphous indium–gallium–zinc–oxide semiconducting channel is systematically investigated. The Al2 O3 interlayer results in not only a good transistor performance with increased on current but also improved gate bias stress stability. The improvement is primarily attributed to a doping effect and mitigation of interface defects. Energy‐band diagrams, experimentally obtained from temperature‐variable electrical characterization and electrostatic force microscopy, validate the channel doping effect, which increase the tunneling probability of the electron charge carriers via a reduction of the Schottky barrier width. A comprehensive study on the influence of various processing parameters, including Al2 O3 thickness, post‐annealing treatment conditions, and types of electrodes, on the transistor device is also performed. This approach guides the practical implementation of stable sol–gel oxide‐based thin‐film transistors and promotes integrated circuitry applications. Abstract : An IGZO transistor with Al2 O3 interlayer demonstrats not only increase on current but also improves gate bias stress stability. Energy‐band diagrams validate the channel doping effect, which increases the tunneling probability of the electron charge carriers via a reduction of the Schottky barrier width. Furthermore, comprehensive study on the influence of various processing parameters is also performed.